NUMBER SENSE SISWA DIKAJI DARI PEMAHAMAN KONSEPTUAL DALAM MATERI PECAHAN DI SEKOLAH MENENGAH PERTAMA - Samosir, Wilin Trifonia; Sugiatno, Sugiatno; Hamdani, Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aims to find out the number of students? sense of fraction material assessed from the level of conceptual understanding. The research method used is descriptive method with a case study form. The research subjects were 29 students. Tools of collecting data in research show that students with high, medium and low levels of conceptual understanding tend to have a moderate category number sense. In general, it can be concluded that number sense of class VII A Students of Junior High School 1 Beduai varies for each level of conceptual understanding. Students with a high level of conceptual understanding have a high number sense category, students with a moderate conceptual level of understanding have a moderate number sense category, and students with a low level of conceptual understanding have a low number sense category. Keywords: Conceptual Understanding, Fraction, Number Sense